Integration of the High-tech and Low-tech in Distance Teacher Training in China: An insight from the Case of Jiangsu Radio and Television University - Zhang, Xiangyang; Hung, Shu-chiu (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
This paper reports the results of a pilot in-service teacher training program undertaken in China from 2001 to 2004. Upon completion, the in-service teachers were awarded a Bachelor of Arts degree (non-honor) specializing in English Language Education. Many interesting findings resulted from this pilot program. By integrating low- and high-technology in the distance in-service teacher training programs, both the trainers (the university lecturers) and the student teachers (in-service school teachers) were able to transform their pedagogical skills. The student teachers learned to become independent learners. The university lecturers learned to adjust their teaching styles to be more learner-centred. Both the lecturers and the student teachers adopted task-based approaches to learning and teaching. Finally, the student teachers were given the means to upgrade their qualifications and teaching skills. Based on these findings, the authors offer suggestions for the future development of student teacher training in China using distance modalities.